Principles of the English Law of Obligations - Burrows, Andrew (Oxford University Press, Incorporated, 2016)
Students will find this book an invaluable overview of the guiding principles of the English law of obligations. Written by a leading team of experts, it covers the central topics of Contract, Tort and Equitable Wrongs, Unjust Enrichment, and Remedies.